BODMAS is used to explain the order of operation in a mathematical expression.

According to the BODMAS rule, the B - brackets are at the highest priority and hence, we will be evaluating all the brackets separately

Solving first bracket:

[3 × {(-5) × (-4)}]

= [3 × 20] = 60 ------------- (1)

Solving second bracket:

{27 + (-13-4)}

=27 + (-17) = 10 -------------- (2)

Solving third bracket :

[{27 × (-2)} ÷ (-3 - 3)]

= [-54 ÷ (-3 - 3)] (since, {27 × (-2)} = -54 )

= [-54 ÷ (-6)] = 9 --------------- (3)

Solving the last breacket

[{(-3) × (-3) × 5} ÷ (-3)]= {45 ÷ (-3)} = -15 (since, (-3) × (-3) × 5} = 45) -------------------- (4)

Substituting the obtained values (1), (2), (3) and (4) in the given expression we get,

[3 × {(-5) × (-4)}] ÷ {27 + (-13 - 4)} + [{27 × (-2)} ÷ (-3 - 3)] + [{(-3) × (-3) × 5} ÷ (-3)]= 60 ÷ 10 + 9 + (-15)

= 6 + 9 - 15

= 6 - 6

= 0

Hence, the value of [3 × {(-5) × (-4)}] ÷ {27 + (-13 - 4)} + [{27 × (-2)} ÷ (-3 - 3)] + [{(-3) × (-3) × 5} ÷ (-3)] is 0

## What is the Value of given expression? [3 × {(-5) × (-4)}] ÷ {27 + (-13 - 4)} + [{27 × (-2)} ÷ (-3 - 3)] + [{(-3) × (-3) × 5} ÷ (-3)]

**Summary:**

The value of the given expression [3 × {(-5) × (-4)}] ÷ {27 + (-13 - 4)} + [{27 × (-2)} ÷ (-3 - 3)] + [{(-3) × (-3) × 5} ÷ (-3)] is 0